(untitled) (Journal of the Bangladesh Agricultural University, 2014)
A field experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh during the period from July to December 2011 to evaluate the effect of variety and placement method of urea super granule (USG) on the yield performance of T. aman rice varieties. The experiment consisted of three aman rice varieties viz., Pajam, BR11, BRRI dhan40 and four placement methods viz., broadcasting method of prilled urea (PU), USG placement by hand, by BAU USG applicator and by BARI USG applicator. The experiment was laid out in a randomized complete block design with four replications. The highest value of grain yield (5.13 t/ha), straw yield (5.90 t/ha) and biological yield (11.04 t/ha) were found in BR11. On the other hand, the lowest grain yield (3.54 t/ha) was produced in variety Pajam. The highest grain and straw yields (5.13 and 5.21 t/ha, respectively) were obtained from the hand placement method of USG. Regarding the interaction of variety and USG placement method, BR11with hand placement method appeared as the best method among others. DOI: http://dx.doi.org/10.3329/jbau.v12i1.21183 J. Bangladesh Agril. Univ. 12(1): 7-12, June 2014